Proceedings of the 42nd Annual ACM SIGPLAN-SIGACT Symposium on Principles of Programming Languages 2015
DOI: 10.1145/2676726.2676983
|View full text |Cite
|
Sign up to set email alerts
|

Higher Inductive Types as Homotopy-Initial Algebras

Abstract: Homotopy Type Theory is a new field of mathematics based on the surprising and elegant correspondence between Martin-Lofs constructive type theory and abstract homotopy theory. We have a powerful interplay between these disciplines -we can use geometric intuition to formulate new concepts in type theory and, conversely, use type-theoretic machinery to verify and often simplify existing mathematical proofs. A crucial ingredient in this new system are higher inductive types, which allow us to represent objects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…So this extension represents one of our main contributions. QW-types generalise prior developments; the internal encodings for particular subclasses of 1-HITs given by Sojakova [25] and Swan [27] are direct instances of QW-types, as the next two examples show. [20,Section 9] give an example of a HIT not constructible in type theory from only pushouts and N. Their HIT F can be thought of as a set of notations for countable ordinals.…”
Section: Quotient-inductive Typesmentioning
confidence: 71%
See 2 more Smart Citations
“…So this extension represents one of our main contributions. QW-types generalise prior developments; the internal encodings for particular subclasses of 1-HITs given by Sojakova [25] and Swan [27] are direct instances of QW-types, as the next two examples show. [20,Section 9] give an example of a HIT not constructible in type theory from only pushouts and N. Their HIT F can be thought of as a set of notations for countable ordinals.…”
Section: Quotient-inductive Typesmentioning
confidence: 71%
“…That unordered countably-branching trees are a QW-type is significant since no previous work on various subclasses of QITs (or indeed QIITs [18,9]) supports infinitary QITs [5,25,27,11,18,9]. See Example 5 for another, more substantial infinitary QW-type.…”
Section: Quotient-inductive Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [van der Weide 2016] a semantics is given for the same class of HITs but with no recursive equality constructors. Sojakova [Sojakova 2015] defines a subset of HITs called W-suspensions by an internal coding scheme similar to W-types. She proves that the induction principle is equivalent to homotopy initiality.…”
Section: Overview Of the Rest Of The Papermentioning
confidence: 99%
“…Higher inductive types were first conceived by participants at the 2011 Oberwolfach workshop on homotopical interpretations of ITT. While an informal description of a general class was given in the HoTT Book [Univalent Foundations Program 2013, ğ6.13], the first rigorous presentation of a large syntactic class was Sojakova's W-quotients [Sojakova 2015], a generalization of W-types which added a path constructor. Sojakova showed that these types are homotopy-initial algebras, building on work on universal characterizations of ordinary inductive types in HoTT by Awodey et al [2012].…”
Section: Free Heterogeneous Compositionmentioning
confidence: 99%